2011
DOI: 10.1016/j.jri.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

New pre-conception immune biomarkers for clinical practice: interleukin-18, interleukin-15 and TWEAK on the endometrial side, G-CSF on the follicular side

Abstract: a b s t r a c tIdentification of biomarkers of optimal uterine receptivity to the implanting embryo as well as biomarkers of oocyte competence would undoubtedly improve the efficiency of assisted reproductive technology (ART). Expression of IL-15 and IL-18 has been shown to be different in patients with failed implantation after IVF/ICSI compared with fertile controls and both correlate with local uNK (CD56+) recruitment and angiogenesis. Tumor necrosis factor weak inducer of apoptosis (TWEAK) has been describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 51 publications
2
21
0
2
Order By: Relevance
“…Our finding that levels of IL-18 were relatively low in unexplained infertility patients might then reflect an underlying perturbed immunological profile for this infertility cause. Importantly, IL-18 has been suggested to favor ovarian folliculogenesis; a positive correlation has been reported between the level of follicular IL-18 and the number of retrieved oocytes and implantation success in women with different etiologies of infertility [29, 30]. Our finding that follicular growth positively correlates with IL-18 levels indirectly supports the role of IL-18 in follicle maturation.…”
Section: Discussionsupporting
confidence: 75%
“…Our finding that levels of IL-18 were relatively low in unexplained infertility patients might then reflect an underlying perturbed immunological profile for this infertility cause. Importantly, IL-18 has been suggested to favor ovarian folliculogenesis; a positive correlation has been reported between the level of follicular IL-18 and the number of retrieved oocytes and implantation success in women with different etiologies of infertility [29, 30]. Our finding that follicular growth positively correlates with IL-18 levels indirectly supports the role of IL-18 in follicle maturation.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, it has been demonstrated that the endometrial levels of IL15 in IVF patients with implantation failure were lower than in the control, suggesting that this cytokine may serve as a potential preconception immune biomarkers for clinical practice (Lédée et al 2011). In agreement with these findings, another recently published study demonstrated a correlation between stromal IL15 and the number of uNK cells.…”
Section: Local Injury-induced Increase In Endometrial Receptivity Is supporting
confidence: 53%
“…On the other hand, IL-15 has also been associated to both unexplained spontaneous abortion [6] and recurrent implantation failure [25]. We, and others, propose that during the preimplantation period, the balance of different cytokines might be more important than their absolute expression per se [23].…”
Section: Discussionmentioning
confidence: 88%